ORIENTASI PEMIKIRAN KIAI PESANTREN DI MADURA - Jazuli, Moh. (Institut Agama Islam Negeri Madura, 2015)
Since the last of 18th century or in the beginning of 19th AD has known intensive interaction between Moslem and the West. In this period, moslems have to face the dilemma, between the wish to revere the Islamic teaching values with the need to follow modern arguments. It causes skripturalis and substansialis thinkings. Through the topic of women leadership, these two thinkings also happen in kiais of pesantren in Sumenep of Madura. Ideologically, both of them are different since their method of meaning to islamic teaching also different. While sosiologically, those are different in thinking the developing social phenomenon. In women leadership, skripturalis kiais keep thinking of forbidding the women of being the leader based onÂ the Qur`an verse and Hadits. On the contrary, substansialis kiais keep thinking of allowing the women in having the public position based on substantial meaning to the Qur`an (al-NisÃ¢:34) and Hadits.Copyright (c) 2015 by KARSA. All right reservedDOI: 10.19105/karsa.v23i2.732